Pembangunan yang Terbayang: Imajinasi Sosio-Teknikal dalam Implementasi Pembangunan Berbasis Komunitas di Indonesia - Hestu Prahara (Antropologi Indonesia, 2018)
This paper discusses the involvement of imagination in the implementation of several techniques for societal improvement introduced by intervention programs in Indonesia. Using the perspective of socio-technical imagination, I contend that the implementation of the World Bank’s Community-Driven Development (CDD) in Indonesia does not only revolve around technical matters, but also structured by collective imagination held by various development actors regarding the formation of desired social order. This paper is part of my reflexivity regarding my involvement as a researcher and filmmaker in a research project designed to evaluate the impact of the implementation of CDD program in health and education sector in Indonesia. The research was conducted from the end of 2016 to the mid of 2017. Based on this experience, this paper examines the way in which imaginations invoked in programs implementation influence the process of film making that involved various development actors ranging from the World Bank’s technocrats in Jakarta, program’s implementer in province, district, sub-district, and village level, to target groups of intervention program in the village.